Relating Invasibility and Invasiveness: Case Study of Impatiens parviflora - Krokaitė, Edvina; Janulionienė, Rasa; Jocienė, Lina; Rekašius, Tomas; Rajackaitė, Giedrė; Paulauskas, Algimantas; Marozas, Vitas; Kupčinskienė, Eugenija (Frontiers in Ecology and Evolution, 2022)
Data on alien species that have been collected for almost a century show that plant invasions are caused by a complex combination of characteristics of invasive species (invasiveness) and characteristics of environment where invasion takes place (invasibility). Impatiens parviflora is one of Europe’s top invasive species. Present study was aimed at integrative evaluation of molecular diversity of populations of highly invasive in Lithuania I. parviflora applying dominant multilocus DNA markers and relating genetic parameters to abiotic and biotic environment, evaluated employing herbaceous plant species. For sampling, urban forests, riparian forests, and agrarian shrubland were selected. Two different DNA-based techniques, Inter Simple Sequence Repeat (ISSR) markers, and Random Amplified Polymorphic DNA (RAPD), were used for detecting genetic variation between 21 populations. Hierarchical analyses of molecular variance at ISSR and RAPD loci revealed significant differentiation of populations depending on geographic zones of the country. Bayesian Structure analyses of molecular data demonstrated existence of many genetic clusters and this finding is in support to multiply introduction of the species. The polymorphism extent at ISSR loci was positively correlated with total coverage of herbaceous plant species. The coverage by I. parviflora was negatively correlated with the total number of herbaceous species and light in the sites. Our results indicate that Lithuanian sites with I. parviflora might be distinguished by high soil nutrient levels. According to the principal component analysis, the coverage by I. parviflora was the most important variable of populations. In conclusion, complexity of invasibility and invasiveness factors determine variability of I. parviflora sites, including genetic traits, coverage of invasive species and conditions of environment that were significant and interrelated.